Non-invasive single-shot imaging for repeated object with highly scattered media - Du, Heng (Nanyang Technological University, 2022)
Scattering media imaging focuses on the reconstruction of hidden objects behind scattering media. In this dissertation, a method for recovering the basic object behind the thick scattering media is proposed. Non-invasive imaging techniques are applied to get high quality ground truth recovery and maintain the integrity of the object to be analyzed. Also, one method to control the memory effect range for two series individual scattering media is proposed.